Burden of Illness and Quality of Life in Tuberous Sclerosis Complex: Findings From the TOSCA Study - Jansen, Anna C.; Vanclooster, Stephanie; de Vries, Petrus J.; Fladrowski, Carla; Beaure d'Augères, Guillaume; Carter, Tom; Belousova, Elena; Benedik, Mirjana P.; Cottin, Vincent; Curatolo, Paolo; Dahlin, Maria; D'Amato, Lisa; et al. (Frontiers in Neurology, 2020)
Research on tuberous sclerosis complex (TSC) to date has focused mainly on the physical manifestations of the disease. In contrast, the psychosocial impact of TSC has received far less attention. The aim of this study was therefore to examine the impact of TSC on health, quality of life (QoL) and psychosocial wellbeing of individuals with TSC and their families. Questionnaires with disease-specific questions on burden of illness (BOI) and validated QoL questionnaires were used. After completion of additional informed consent, we included 143 individuals who participated in the TOSCA (TuberOus SClerosis registry to increase disease Awareness) study. Our results highlighted the substantial burden of TSC on the personal lives of individuals with TSC and their families. Nearly half of the patients experienced negative progress in their education or career due to TSC (42.1%), as well as many of their caregivers (17.6% employed; 58.8% unemployed). Most caregivers (76.5%) indicated that TSC affected family life, and social and working relationships. Further, well-coordinated care was lacking: a smooth transition from pediatric to adult care was mentioned by only 36.8% of adult patients, and financial, social and psychological support in 21.1%, 0% and 7.9% respectively. In addition, the moderate rates of pain/discomfort (35%) and anxiety/depression (43.4%) reported across all ages and levels of disease demonstrate the high BOI and low QoL in this vulnerable population.